The Influence of Agile Leadership and Innovative Behavior on MSMEs Performance in Karawang - Budi Santoso; Anggi Pasca Arnu; Sobandi, Ade (Universitas Ibn Khladun Bogor, 2024)
MSMEs are indispensable in the economic landscape of both developing and developed countries. Their ability to innovate, generate employment, and contribute to regional development makes them crucial for sustainable and inclusive economic growth. Addressing the challenges faced by MSMEs, particularly in accessing finance, skilled manpower, and technology, is crucial to maximizing their potential. This study aims to analyze the influence of agile leadership and innovative behavior on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Karawang. Research methodology this research is quantitative research with descriptive analysis and multiple linear regression analysis. Sample in this study was 100 MSMEs in the home industry who have been running their businesses for 3 years or more. The data collection tool used a questionnaire distributed via Google Form. The findings show that there is a positive influence between agile leadership and innovative behavior variables on MSMEs performance. The partial relationship between agile leadership on MSMEs performance is 9.3%. Then the partial relationship between innovative behavior on MSMEs performance is 26.9%. In addition, the results of the simultaneous relationship between agile leadership and innovative behavior are 70.9%, while the other 29.1% is influenced by other variables not studied. The study concluded that innovative behavior has a more dominant influence than agile leadership. The results of this study underscore the importance of fostering agile leadership and innovative behavior to improve the performance of MSMEs in a dynamic business environment.